Demographic correlates of low haemoglobin deferral among potential blood donors in South Africa - Kuonza, Farisai (My University, 2016)
Introduction Blood transfusion is important in the management of many diseases. Approximately 20% of all potential blood donors are deferred from giving blood for various reasons. Low haemoglobin potential donor deferral is the single major cause of donor deferral and it accounts for about 10% of all deferrals (1). Understanding factors associated with low haemoglobin potential donor deferral could help in reducing deferrals and increase blood supply. Literature on correlates of low haemoglobin deferral is sparse in South Africa. The aim of the study was to determine the prevalence of low haemoglobin deferral among potential donors, proportion of low haemoglobin deferral among deferred donors and to identify factors associated with low haemoglobin donor deferral in potential blood donors in eight provinces of South Africa in 2013. Methods The study was a cross sectional analysis of secondary data collected from eight South African provinces in 2013. There were a total of 996 060 attempted blood donations from 471 126 potential donors. Analysed sample consisted of 8056 random sampled donors (representing 2% of the potential blood donors aged 18 and above). Prevalence of low haemoglobin donor deferral among potential donors and proportion of low haemoglobin donor deferral among deferred donors were estimated. Binomial and multinomial logistic regression analyses were used to identify the factors associated with low haemoglobin donor deferral. Results Among the 8056 potential donors, 51.9% were females and the overall median age of all potential donors was 32 years (IQR: 23-45). About half (49.3%) of all the potential donors were repeat donors, 26.4% were re-join and 24.3% were first time donors. The potential donors of blood group O were 43.8% of the population, followed by blood group A (29.4%) while blood group B and AB were 14.9% and 4.4%, respectively. The overall prevalence of donor deferral was 22.7% (95% CI: 21.8-23.7), while the prevalence of deferral due to low haemoglobin was 6.7% (95% CI: 6.1-7.2). Potential donors of female gender, 18-25 age group, Black race, first time donors and those that donated in Kwa-Zulu Natal had the highest low haemoglobin prevalence. The proportion attributable to low haemoglobin among potential donors was 0.29. In adjusted analysis the factors associated with low haemoglobin deferral were sex (P<0.001), donor type (P<0.001), province (P<0.001) and race (P<0.001). Conclusion The prevalence of low haemoglobin donor deferral obtained was 6.7%. The proportion of deferral due to haemoglobin among deferred donors was 0.29 and the identified correlates are sex, donor type, province and race. The identified correlates could be used when deciding which potential donors to invite for a blood donation after each inter-donation interval has elapsed and blood supply could be increased.
A research report submitted to the Faculty of Heath Sciences, University of Witwatersrand, Johannesburg in partial fulfilment of the requirements of the degree of Master of Science in Epidemiology (Epidemiology and Biostatistics) 19 October 2015